Dynamic aspects of cell surface organization - Poste, George; Nicolson, Garth L. (Cell surface reviews, 1977)
Cell Surface Reviews, Volume 3: Dynamic Aspects of Cell Surface Organization reviews the progress in the study of the dynamic nature of membrane organization. The book is comprised of 14 chapters that discuss the various areas of concerns relating to membrane dynamics. The coverage of the text includes techniques and methods employed in the analysis and manipulation of the various aspects of cell membranes, such as freeze-fracture techniques; manipulation of the lipid composition of cultured animal cells; and somatic genetic analysis. The book also talks about some of the traits and behaviors.